Effects of Lupeol on Intestinal Anastomosis After Experimental Intestinal Ischemia-Reperfusion Injury in Rats - Kaya C; Kapisiz A; Eryilmaz S; Karabulut R; Turkyilmaz Z; Inan MA; Aydin GY; Celik MA; Sonmez K (Drug Design, Development and Therapy)
Cem Kaya,1 Alparslan Kapisiz,1 Sibel Eryilmaz,1 Ramazan Karabulut,1 Zafer Turkyilmaz,1 Mehmet Arda Inan,2 Gizem Yaz Aydin,3 Mert Alperen Celik,4 Kaan Sonmez1 1Department of Pediatric Surgery, Faculty of Medicine, Gazi University, Yenimahalle, Ankara, Turkey; 2Department of Pathology, Faculty of Medicine, Gazi University, Yenimahalle, Ankara, Turkey; 3Department of Biochemistry, Faculty of Medicine, Gazi University, Yenimahalle, Ankara, Turkey; 4Faculty of Medicine, Gazi University, Yenimahalle, Ankara, TurkeyCorrespondence: Cem Kaya, Medical Faculty, Gazi University, Department of Pediatric Surgery, Emniyet Mahallesi, Mevlana Bulvarı, No: 29, Yenimahalle, Ankara, 06500, Turkey, Tel +90 312 2026213, Fax +90 312 2230528, Email drcemkaya61@gmail.comBackground: Intestinal ischemia/reperfusion (I/R) injury can occur in a wide variety of diseases and surgeries. If necessary, the blood flow should be restored, including re-anastomosis by removing the intestines with impaired circulation. In this process, anastomotic strength is as important as inflammatory responses and oxidative stress. Therefore, we conducted the study to investigate the effects of lupeol on intestinal ischemia-reperfusion injury, not only biochemically and histopathologically but also on anastomotic strength and miRNAs.Methods: Female rats were randomly divided into six groups. While only laparotomy was performed in the control group (Group C), anastomosis was performed in the sham group (Group S). In the other groups, the superior mesenteric artery was clamped for 45 minutes. In the groups I/R1 and L1, the intestine was transected, and end-to-end anastomosis was performed at the 1st hour of reperfusion. In the groups I/R24 and L24, this procedure was performed at the 24th hour of reperfusion. In addition, lupeol treatment was given before reperfusion and for the following 4 days in the groups L1 and L24. All rats, except the control group, bursting pressure was measured on the 5th day of anastomosis, and then all rats including the control group were sacrificed. TNF-α, IL-6 levels in blood samples and MDA, GSH, caspase-3, miR-29b-3p, miR-34a-5p, miR-495-3p levels in intestinal tissues were measured, and intestinal histopathology was also examined.Results: Lupeol treatment, which was statistically significant in some parameters, demonstrated positive effects by decreasing TNF, IL-6, MDA, caspase-3, histopathological damage levels and increasing GSH and bursting pressure. In addition, lupeol decreased miR-34a-5p expression and increased miR-29b-3p and miR-495-3p expression.Conclusion: Lupeol protected the intestines from I/R damage with its antioxidant and anti-inflammatory effects. Besides, it reduced the histopathological damage and increased the anastomotic strength. Additionally, miR-29b-3p, miR-34a-5p, miR-495-3p expressions were altered by lupeol.Keywords: lupeol, ischemia/reperfusion injury, small intestine, miR